RNA polymerase I inhibition induces terminal differentiation, growth arrest, and vulnerability to senolytics in colorectal cancer cells. Issue 15 (1st July 2022) - Otto, Christoph; Kastner, Carolin; Schmidt, Stefanie; Uttinger, Konstantin; Baluapuri, Apoorva; Denk, Sarah; Rosenfeldt, Mathias T.; Rosenwald, Andreas; Roehrig, Florian; Ade, Carsten P.; Schuelein‐Voelk, Christina; Diefenbacher, Markus E.; et al.
Abstract : Ribosomal biogenesis and protein synthesis are deregulated in most cancers, suggesting that interfering with translation machinery may hold significant therapeutic potential. Here, we show that loss of the tumor suppressor adenomatous polyposis coli (APC), which constitutes the initiating event in the adenoma carcinoma sequence for colorectal cancer (CRC), induces the expression of RNA polymerase I (RNAPOL1) transcription machinery, and subsequently upregulates ribosomal DNA (rDNA) transcription. Targeting RNAPOL1 with a specific inhibitor, CX5461, disrupts nucleolar integrity, and induces a disbalance of ribosomal proteins. Surprisingly, CX5461‐induced growth arrest is irreversible and exhibits features of senescence and terminal differentiation. Mechanistically, CX5461 promotes differentiation in an MYC‐interacting zinc‐finger protein 1 (MIZ1)‐ and retinoblastoma protein (Rb)‐dependent manner. In addition, the inhibition of RNAPOL1 renders CRC cells vulnerable towards senolytic agents. We validated this therapeutic effect of CX5461 in murine‐ and patient‐derived organoids, and in a xenograft mouse model. These results show that targeting ribosomal biogenesis together with targeting the consecutive, senescent phenotype using approved drugs is a new therapeutic approach, which can rapidly be transferred from bench to bedside. Abstract : Loss of APC, the initiating event in the adenoma carcinoma sequence for CRC, induces the expression of RNAPOL1, and subsequently upregulates rDNA transcription. Targeting RNAPOL1 with a specific inhibitor, CX5461, disrupts nucleolar integrity, induces imbalance of ribosomal proteins, irreversible growth arrest with features of senescence and terminal differentiation. This inhibition of RNAPOL1 renders CRC cells vulnerable towards senolytic agents.